Assessment of the Environmental Impact of Fly Ash on the Concentration of Heavy Metals around Cement Company of Northern Nigeria (Lafia Journal of Scientific and Industrial Research, 2024)
This study assessed the impact of Coal Fly Ash on the concentration of Heavy metals in water, soil, and vegetables (moringa and spinach) in the environment of Cement Company of Northern Nigeria. The samples collected were digested, and analysed for heavy metals concentration using Atomic Absorption Spectroscopy. The concentrations of heavy metals obtained in water samples were higher than the WHO/SON permissible limit, except for Cu and Zn which are below the standard limits. The average concentration of Pb, Mn, Cd, and Ni in all plant samples was higher than the permissible limit, except Cd in spinach sample. The roots of the spinach accumulate higher concentrations of heavy metals than the leaves and stem, while leaves of moringa accumulate higher than the roots and stem. The concentration of heavy metals in soil sample was below the WHO limit. Comparatively the plants samples have the highest concentrations of heavy metals than the water and soil samples. The coal fly ash from the Cement Company must have contributed to the significant concentration of Heavy metals in the environment making the water and plants from the study area unfit for human and animal consumption.